The Relationship between Binge Watching Korean Dramas and Insomnia Incident in Students at Nusa Cendana University, Kupang, Indonesia - Florensiana Hariyati Eho; Indriati A. Tedju Hinga; R. Pasifikus Christa Wijaya (Journal of Health Promotion and Behavior, 2023)
Background: Insomnia is a condition where a person has difficulty in sleeping, especially sleeping at night. Insomnia is a health problem that is often found in all environments, both in developed and developing countries. Binge watching is the activity of continuously watching a program. Because they are used to watching continuously, people can feel uneasy if they miss an episode of the series they are watching. This study aimed to determine the relationship of binge-watching Korean dramas with the incidence of insomnia in students at Nusa Cendana University, Kupang.Subjects and Method: A cross-sectional study was conducted at Nusa Cendana University, Kupang, East Nusa Tenggara, Indonesia, from September to October 2022. A total of 428 students were selected in this study. The dependent variable was insomnia and the independent variable was Korean drama. Data were collected using a questionnaire and analyzed with the Spearman correlation statistical test.Results: Binge-watching Korean dramas is associated with the incidence of insomnia, and it is statistically significant (r= 0.629; p<0.001).Conclusion: Binge-watching Korean dramas is related to the incidence of insomnia.Keywords: binge-watching, korean drama, insomnia, student.Correspondence:Florensiana Hariyati Eho. Public Health Study Program. Faculty of Public Health Universitas Nusa Cendana Kupang. Jl. Adisucipto Penfui, Kupang, 881580 East Nusa Tenggara. Email: lauraeho31@gmail.com. Mobile: +62 812-3863-5371.Journal of Health Promotion and Behavior (2023), 08(01): 53-57DOi: https://doi.org/10.26911/thejhpb.2023.08.01.07